Investigation of bromination reactions using organic ammonium tribromide and their applications towards bioactive natural products synthesis - Bose, Gopal (My University, 2002)
This dissertation describes the successful and unsuccessful results for the preparation of various a-bromoenones from their corresponding acyclic and cyclic enones using organic ammonium tribromides; synthesis of various ring substituted flavones and aurones (which are structurally isomeric with flavones) from their corresponding 2ं-acetoxychalcones by bromination, followed by cyclisation as well as synthesis of 7-bromoaurones and 8-bromoflavones from 2ं-hydroxychalcones. Chapter 1 of this dissertation includes the review on a-bromoenone, a-bromo-2ं-acetoxychalcone and their applications towards the synthesis of flavone. Chapter 2 in part I describes the results of our successful efforts on the preparation of both acyclic and cyclic a-bromoenones from the corresponding enones in one pot, by bromination using organic ammonium tribromide (OATB), followed by dehydrobromination by employing...
Chaudhuri, Mihir Kanti
Keywords: CHEMISTRY